The role of inexperience in motorcycle crashes among novice and returning motorcycle riders. (September 2022) - Goodwin, Arthur H.; Wang, Yudan Chen; Foss, Robert D.; Kirley, Bevan
Highlights: Crash rates peak for both younger novice and older novice/returning motorcycle riders immediately after licensure, and decline rapidly afterwards. The improvement rate (IR) for younger novice riders is 0.42; that is, the crash rate for younger novices declines by approximately 42% as experience doubles. The crash curve for novice motorcyclists is similar to that of novice car drivers and is consistent with a learning process. Abstract: Objectives: To examine the crash trends of younger novice and older novice/returning motorcycle riders. Methods: We used a linked database of North Carolina crash and licensing data from 1991 through 2018 that included 103, 142 younger novice and 98, 540 older novice/returning motorcycle riders. We examined the percent of riders who crashed each month after obtaining a motorcycle license. Results: Crash rates peak for both younger novice and older novice/returning motorcycle riders immediately after licensure. Crash rates decline rapidly, and the rate of decrease resembles a power function. The improvement rate (IR) for younger novice riders is 0.42; that is, the crash rate for younger novices declines by approximately 42% as experience doubles. Conclusion: The crash curve for novice motorcyclists is similar to that of novice car drivers and is consistent with a learning process. Practical Applications: The crash trends of novice motorcycle riders indicate that current training, licensing, and educational efforts are not adequately preparing new riders. Additional efforts to develop more effective training, and research to inform a well-calibrated graduated licensing process for new riders are needed.